Justice Delayed: The Right to Effective Remedy for Victims of Coercive Sterilization in the Czech Republic - Cahn, Claude (Health and human rights, 2017)
Tens of thousands of women were coercively sterilized in Czechoslovakia and its successor states. Romani women were particularly targeted for these measures. These practices stopped only in 2004, as a result of international pressure. Although some measures have been taken to ensure that these practices are not repeated, to date neither the Czech Republic nor Slovakia have completed the work of providing effective remedy to victims, as is their right. This article focusses on efforts in the Czech Republic. It concludes that, inter alia, an administrative mechanism is needed to provide financial compensation to victims, since the road to remedy via courts is effectively blocked.
Keywords: sociální spravedlnost; Coercion; Compensation and Redress; Female; Sterilization, Involuntary; kompenzace a odškodnění; Humans; ženské pohlaví; Česká republika; lidé; sterilizace nedobrovolná; Social Justice; nátlak; Czech Republic